The answer is -3 because you’re plugging g(x) into f(x). For every x there is in f(x), plug in g(x)’s equation. After you get another equation (simplified), which is x^2 -7x -11, plug -1 for every x and condense.
Answer:
21
Step-by-step explanation:
0 + 1 = 1
1 + 2 = 3
3 + 3 = 6
6 + 4 = 10
10 + 5 = 15
15 + 6 = 21
Each number is added to an increase of 1 - first add 1, then add 2, then add 3,etc
Not listed but next would be 21 + 7 = 28
so it would be 0, 1, 3, 6, 10, 15, 21, 28
Answer:
<h3>B. 4units</h3>
Step-by-step explanation:
Find the diagram attached. The diagram is a similar triangle.
From the diagram, XZ/XY = CA/AB
Given XZ = 2x-2+2x-2 = 4x-4
XY =5x-7
CA = 2x-2
AB= x+1
On substituting this parameters into the formula to get x first
4x-4/5x-7 = 2x-2/x+1
cross multiply
(4x-4)(x+1) = 5x-7(2x-2)
open the parenthesis
4x²+4x-4x-4 = 10x²-10x-14x+14
4x²-4 = 10x²-24x+14
10x²-4x²-24x+14+4 = 0
6x²-24x+18 = 0
x²-4x+3 = 0
x²-3x-x+3 = 0
x(x-3)-1(x-3) =0
(x-3)(x-1) = 0
x = 3 and 1
Next is to get length AX.
Given AX = 2x-2
Substitute x = 3 into the expression
AX = 2(3)-2
AX = 6-2
AX = 4 units
Hence the measure of length AX is 4 units
The triangles are similar by the SSS (side-side-side) similarity theorem because the sides of the two triangles are in proportion (5/15 = 3/9 = 4/12)
Hope this helps =)